2022
DOI: 10.1101/2022.02.21.481289
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cochlear theta activity oscillates in phase opposition during interaural attention

Abstract: It is widely established that sensory perception is a rhythmic process as opposed to a continuous one. In the context of auditory perception this effect is only established on a cortical and behavioral level. Yet, the unique architecture of the auditory sensory system allows its primary sensory cortex to modulate the processes of its sensory receptors at the cochlear level. Previously, we could demonstrate the existence of a genuine cochlear theta (~6 Hz) rhythm that is modulated in amplitude by intermodal sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(137 reference statements)
1
0
0
Order By: Relevance
“…This idea is supported by recent evidence in humans demonstrating a top-down modulation of the auditory periphery by selective attention (e.g. Gehmacher et al, 2022;Köhler et al, 2021;Köhler & Weisz, 2022) and could also explain why, in the current study, we observed the reported ocular speech tracking effects even without any meaningful visual information. Further studies could investigate potential effects / benefits of matching visual input (videos), e.g.…”
Section: Gaze and Prioritization Of Spectrotemporal Acoustic Informationsupporting
confidence: 91%
“…This idea is supported by recent evidence in humans demonstrating a top-down modulation of the auditory periphery by selective attention (e.g. Gehmacher et al, 2022;Köhler et al, 2021;Köhler & Weisz, 2022) and could also explain why, in the current study, we observed the reported ocular speech tracking effects even without any meaningful visual information. Further studies could investigate potential effects / benefits of matching visual input (videos), e.g.…”
Section: Gaze and Prioritization Of Spectrotemporal Acoustic Informationsupporting
confidence: 91%